2014
DOI: 10.1016/s2095-3119(13)60504-3
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of Soil Trace Elements Distribution and Soil-Plant-Animal Continuum in Relation to Trace Elements Status of Sheep in Huangcheng Area of Qilian Mountain Grassland, China

Abstract: The purpose of the present study was to survey contents of trace elements of Cu, Mn, Fe, and Zn in the surface layer (0-20 cm) in the soil, pasture and serum of sheep in Huangcheng area of Qilian mountain grassland, China. Also the soil-plant-animal continuum was analyzed. Soil (n=300), pasture (n=60), and blood serum samples from sheep (n=480) were collected from Huangcheng area of Qilian mountain grassland, China. The contents of trace element in the samples were analyzed by atomic absorption spectrophotomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…However, such correlations were not found between the mineral levels in sheep and in soil except for Na (0.75), Fe (0.91), Mn (0.97), and Zn (0.94). The findings under this study are opposite to those reported by Wang [11], who re ported that no correlations were found between soil, herbage, and blood of sheep in Huangcheng area of Qilian Mountains. Under this current study, regression of minerals in soils and herbage revealed positive linear relationships; however, the correlation values are too small except for Ca, P, Na, Fe, Mn, and Zn.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, such correlations were not found between the mineral levels in sheep and in soil except for Na (0.75), Fe (0.91), Mn (0.97), and Zn (0.94). The findings under this study are opposite to those reported by Wang [11], who re ported that no correlations were found between soil, herbage, and blood of sheep in Huangcheng area of Qilian Mountains. Under this current study, regression of minerals in soils and herbage revealed positive linear relationships; however, the correlation values are too small except for Ca, P, Na, Fe, Mn, and Zn.…”
Section: Discussioncontrasting
confidence: 99%
“…When grazing, the mineral elements in soil and herbage will eventually be reflected in livestock [11]. The mineral ele ments in herbage has a crucial influence on the content and balance of mineral elements in livestock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a research conducted in a mountainous region in China on healthy sheep serum, the levels of Cu, Mn, Fe, Zn elements were found as (0.2, 0.2, 7.0, 1.9µg/ mL), respectively (Wang, 2014). Furthermore, in studies in which the sheep samples were used by many researchers (Miedico et al, 2016), the serum Cu levels were determined as 0.8 and 1.2 g/mL, and the Zn levels as 6.9 and 14.8 µg/ mL.…”
Section: Resultsmentioning
confidence: 99%
“…After that the samples were digested using microwave digestion system (MARS5, CEM Company, America). The optimal digestion procedure was described in our previous publication (Wang et al, 2014a). The digested samples were cooled to room temperature, transferred to glass tube, and removed the diacid mixture until 1mL was left using intelligent temperature controller in 130°C.…”
Section: Processing and Digestion Of Samplesmentioning
confidence: 99%